Supramolecular Agent–Simulant Correlations for the Luminescence Based Detection of V‐Series Chemical Warfare Agents with Trivalent Lanthanide Complexes. Issue 9 (1st March 2016) - Dennison, Genevieve H.; Bochet, Christian G.; Curty, Christophe; Ducry, Julien; Nielsen, David J.; Sambrook, Mark R.; Zaugg, Andreas; Johnston, Martin R.
Abstract: Solution spectroscopic investigations into the interactions of eight potential bidentate V‐series organophosphorus chemical warfare agent (OP CWA) simulants with [Eu(phen)2 (NO3 )3 ]· 2H2 O demonstrated that the chemical and structural composition of the secondary binding site within the simulant was of paramount importance. Only simulants containing both phosphoryl/phosphonyl and amine moieties generated analogous spectroscopic behaviours to V‐series OP CWAs seen in previous studies. The results demonstrated that the bidentate chelation mechanism was driven by the phosphoryl/phosphonyl moieties and that the presence of the amine moieties induced a significant secondary dynamic luminescence quenching mechanism. The binding modes of the simulants VO and TEEP to trivalent lanthanides (Eu and La) were further investigated using 1 H and 31 P NMR spectroscopic titrations and kinetic IR experiments. VO, with both the phosphonyl and amine binding sites was found to be the most appropriate simulant for V‐series OP CWAs in supramolecular studies with trivalent lanthanide ions and we recommend VO for use in supramolecular studies of this type. Abstract : Solution spectroscopic investigations with potential bidentate V‐series OP CWA simulants with [Eu(phen)2 (NO3 )3 ]· 2H2 O demonstrated the interaction and luminescence quenching mechanism to be specific and selective for bidentate systems containing both amine and phosphoryl/phosphonyl moieties. Only the low toxicity V‐series simulant VO generated analogous spectroscopic behaviours to the OP CWAs VX and VG.